Perception of Malaysian higher education institutions' academic executive staff on followership styles, leadership development and quality management - Ibrahimi, Mensur (Kulliyyah of Education, International Islamic University Malaysia, 2017)
The main purpose of this study is to investigate what academic executive staff in selected Peninsular Malaysian universities perceived on their followership styles, leadership development and quality management system cultured and implemented in their institutions. Secondly, the study is to measure the mediating function of the quality management system on the relationships between the followership styles and the leadership development. Furthermore, the study aims to investigate the degree of prediction of followership styles on leadership development function as well as to test if the integrated followership styles and leadership development (IFLD) model is valid and reliable. The participants of the study are 395 selected academic executive staff from eight selected established public universities in Peninsular Malaysia. Exploratory factor analysis (EFA) was used to determine the underlying factors, followed by the employment of confirmatory factor analysis (CFA). Finally a full fledge structural equation modelling (SEM) was employed to address all the research questions and hypothesis testing. The study revealed the presence of the followership styles, leadership development and quality management system in the universities concerned. The study also revealed the presence of significant relationship (.05 level) between followership styles, quality management system and leadership development both from Western and Islamic perspectives. There was quite significant empirical evidence of Islamic followership styles prediction on Islamic leadership development. The study also proved that the modified IFLD model was valid and reliable. The findings from this study might be able to provide clear guidelines in helping higher educational leaders and managers better understand how to benefit most from their followers in the process of leadership development endeavours. This study is considered one of the first attempts in exploring the relationship and meeting points in (FS) and (LD) between the Islamic and Western perspectives.